Legal Instruments for the Protection of Migrant Workers by ASEAN and Indonesia National Law - Jelly Leviza; Ningrum Natasya Sirait; T. Keizerina Devi (Proceedings of AICS - Social Sciences, 2016)
The existence of ASEAN as an international organization with legal personality was referring to the birth of the ASEAN Charter, 2007. The Charter became effective on December 15,2008 that Indonesia has ratified by Law No. 38 Year 2008. The Charter emphasizes the commitment of regional cooperation within the framework of the ASEAN Community basedon three pillars: political security, economic and socio-cultural. The three pillars areinterrelated for the purpose of peace, stability and prosperity in the ASEAN. One area that was agreed by ASEAN is legal protection for migrant workers. Legal protection for migrant workers is important because of some cases of abuse and torture by the employer, as in the case of Siti Hajar 2009. For the Indonesian legal protection for migrant workers is urgent because the number of migrants is increasing every year and it is the Government's obligation to protect its citizens wherever existence. ASEAN, in the regional level already has legal instruments for the protection of migrant workers namely the ASEAN Declaration of the Protection and the Promotion of the Rights of Migrant Workers. While at the national level, Indonesia has a number of legal instruments related, that is Law No. 13 Year 2003 and Law No. 39 Year 2004 on the Placement and Protection of Indonesian Workers Abroad. Based on the above, this paper will examine first, the protection of the rights of migrant workers within the framework of the ASEAN agreement and the second will examine the comparison between the protections of the rights of migrant workers in ASEAN level with Indonesia national law. The goal is to determine the harmonization and synchronization of the legal protection of migrant workers in ASEAN perspective and the perspective of Indonesian national law.